2002
DOI: 10.1006/bbrc.2002.6431
|View full text |Cite
|
Sign up to set email alerts
|

The EGF-like Homeotic Protein dlk Affects Cell Growth and Interacts with Growth-Modulating Molecules in the Yeast Two-Hybrid System

Abstract: Levels of dlk, an EGF-like homeotic protein, are critical for several differentiation processes. Because growth and differentiation are, in general, exclusive of each other, and increasing evidence indicates that Dlk1 expression changes in tumorigenic processes, we studied whether dlk could also affect cell growth. We found that, in response to glucocorticoids, Balb/c 3T3 cells with diminished levels of dlk expression develop foci-like cells that have lost contact inhibition, display altered morphology, and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 53 publications
(66 reference statements)
1
40
1
1
Order By: Relevance
“…In response to glucocorticoids, Balb/c 3T3 cells had diminished levels of DLK1 and grew faster (Baladron et al, 2002). In addition, Gaetano et al (1992) found that the neuroblastoma cell line SMS-KCNR, cultured with dibutyryl cyclic AMP (dbcAMP), had a markedly increased expression of DLK1 associated with a transition to a more mature chromaffin phenotype with no change in the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In response to glucocorticoids, Balb/c 3T3 cells had diminished levels of DLK1 and grew faster (Baladron et al, 2002). In addition, Gaetano et al (1992) found that the neuroblastoma cell line SMS-KCNR, cultured with dibutyryl cyclic AMP (dbcAMP), had a markedly increased expression of DLK1 associated with a transition to a more mature chromaffin phenotype with no change in the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases PGRN binds its partner weakly, with affinities in the micromolar range, (94,95) and associates with the target protein through an EGF-containing module. PGRN reportedly binds the membrane protein Dlk, (96) which is also rich in EGF modules, and although not yet tested, an affinity for EGF modules may prove a recurrent pattern in PGRN-protein interactions. Interactions of PGRN with intracellular proteins such as cyclin T have been reported, although their physiological significance is uncertain.…”
Section: Progranulin Interaction With Other Proteinsmentioning
confidence: 98%
“…For all experiments, C2C12 cells were seeded at 10,000 cells/cm 2 and cultured for 48 hours before further treatment. For transfection experiments, cells were equilibrated in serum-free medium for 1 hour prior to transfection for 4 hours with 1 µg/12-well pCD2-Dlk1FL (containing full-length mouse Dlk1 cDNA (Baladrón et al, 2002) or control pCD2 vector using the Lipofectamine 2000 protocol (Life Technologies, Denmark). Immediately following transfection, cells were induced to differentiate in DMEM + 2% horse serum + 1% PS for 5 days.…”
Section: Overexpression Of Dlk1 In the Myogenic Cell Line C2c12mentioning
confidence: 99%